The Effect of U-Dictionary on Vowel Pronunciation Ability of the Tenth Grade Students - Krismonika; Maida Norahmi; Natalina Asi (The Study Program of English Education of Palangka Raya University, 2021)
The objective of this research was to find out the empirical data which could determine whether there is a significance of using U-Dictionary application on vowel pronunciation ability of the tenth-grade students of SMA Kristen Palangka Raya or not. The method used quantitative with pre-experimental research method with One Group Pretest-Posttest Design. The samples of this research were 30 students of the tenth grade. The samples were selected by total sampling. To collect the data, this research used a pronunciation test which had been tried out provided in pretest and posttest as the research instrument. The result of this research revealed that the mean score of the posttest was greater than that of the pretest, namely 66.33 > 49.17. Then the result of hypotheses testing showed that the critical value for the one-tailed test is ta with df = n-1, 30-1 = 29. The value of the test statistic, is t* = -6.809 and the critical value of t0 is t.05 29 = - 1.699. Because t*< t.05 29 = -6.809 < -1.699, we reject H0. The test results were statically significant at the 5% level. It means that there is a significant effect of using the U-Dictionary application on the vowel pronunciation ability of the students of SMA Kristen Palangka Raya.